2011
DOI: 10.1016/j.abb.2010.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Structural biology of redox partner interactions in P450cam monooxygenase: A fresh look at an old system

Abstract: The P450cam monooxygenase system consists of three separate proteins: the FAD-containing, NADH-dependent oxidoreductase (putidredoxin reductase or Pdr), cytochrome P450cam and the 2Fe2S ferredoxin (putidaredoxin or Pdx), which transfers electrons from Pdr to P450cam. Over the past few years our lab has focused on the interaction between these redox components. It has been known for some time that Pdx can serve as an effector in addition to its electron shuttle role. The binding of Pdx to P450cam is thought to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 66 publications
(106 reference statements)
0
45
0
Order By: Relevance
“…However, since CPR affinity is measured indirectly through substrate turnover, it is not possible to distinguish the effect of mutagenesis on protein activity from CPR-P450 complex formation by relying exclusively on steady-state measurements. Additionally, the significant biochemical and crystallographic work performed on the P450cam and P450BM3 redox complexes suggests the likelihood that ionic interactions do not exclusively dominate protein-protein contact regions in all P450s(18). The structure between the heme domain of P450BM3 and its FMN domain is the only available P450-redox partner complex structure and reveals that only a single intermolecular ionic bond mediates domain interaction(19).…”
mentioning
confidence: 99%
“…However, since CPR affinity is measured indirectly through substrate turnover, it is not possible to distinguish the effect of mutagenesis on protein activity from CPR-P450 complex formation by relying exclusively on steady-state measurements. Additionally, the significant biochemical and crystallographic work performed on the P450cam and P450BM3 redox complexes suggests the likelihood that ionic interactions do not exclusively dominate protein-protein contact regions in all P450s(18). The structure between the heme domain of P450BM3 and its FMN domain is the only available P450-redox partner complex structure and reveals that only a single intermolecular ionic bond mediates domain interaction(19).…”
mentioning
confidence: 99%
“…P450cam catalyzes the hydroxylation of D-camphor to 5-exohydroxycamphor using two electrons, two protons, and molecular oxygen. Putidaredoxin (Pdx) reductase oxidizes NADH and transfers the electrons to Pdx, which, in turn, shuttles electrons to P450cam in two consecutive steps (3)(4)(5). This complex reaction is controlled by the enzyme to ensure an efficient coupling between dioxygen reduction and substrate hydroxylation and to avoid side reactions.…”
mentioning
confidence: 99%
“…However, depending on the identities of the surface residues of the individual P450s, non-charged attractions including hydrophobic and intermolecular hydrogen bonding interactions have also been suggested to be dominant factors in stabilizing the binding of the hemoprotein to the flavoprotein (16, 32-34). Thus, by comparing the differential effect of PN on P450 reduction to give the reduced P450-CO spectrum by NADPH/CPR to that by dithionite as well as the differential effect of PN on the BHP- and CPR-dependent catalytic activities, we concluded that nitrotyrosine formation on the proximal side of CYP3A4 impairs its interaction with CPR.…”
Section: Discussionmentioning
confidence: 99%